„Wieś dla dzieci” – akcja Rady Głównej Opiekuńczej w latach 1916–1920 - Przeniosło, Małgorzata (Zeszyty Wiejskie, 2016)
The “Countryside For Children” campaign was organized by the Central Welfare Council, one of the largest self-help organizations in Poland during the World War I and after the armistice. The aim of the campaign was to send poor children from major cities to the countryside in order to improve their food supply and health. In most cases, they remained in the country for at least several months. The children were placed both with individuals who wanted to host them and take care of them, as well as in shelters, specially organized by the CWC. Throughout the campaign almost 30 thousand children received support.